Perceived Causes and Solutions of the Translation Problem in Management Research - Shapiro, Debra L.; Kirkman, Bradley L.; Courtney, Hugh G. (Academy of Management Journal, 2007)
The article discusses problems in translating research about private and public sector management from theory into practice. The authors suggest that Academy of Management members should change their knowledge transfer and production processes to close the gap between theory and practice. These changes could include altering editorial policies at management journals and awarding publications that have a significant impact on management practice. Other solutions include encouraging collaborations between researchers and practitioners.